WATER QUALITY OF BATANG ARAU ESTUARY PADANG, WEST SUMATERA BASED ON ORGANIC MATERIAL CONTAINERS - Dianti Farhana Kamasela; Bintal Amin; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Marine pollution is a change in marine environment including estuaries, which can cause bad consequences for marine living resources, danger to human health and reduce the quality of sea water and it’s function. This research aims to know the water quality of Batang Arau River and it’s organic pollution level. This research was held on December 2016 until February 2017 by using survey method. The quality of Batang Arau River is categorized as under adverse conditions. Based on this observation, found many garbage which makes the value of dissolved oxygen are low (DO <5 mg/L) and it’s not eligible for biota’s life. The value of BOD in Batang Arau River ranged from 0.2-2.1 mg/L, the value of COD range from 12.8-53.3 mg/L and the value of TOM ranged from 12.20-22.12 mg/L. The result of ANOVA shows that value of the water quality in Batang Arau River are very different between stations (p<0.001).Keywords: Organic pollution, Batang Arau River, Water Quality